The Effect of Discretionary Bonuses on Employee Performance through Organizational Justice and Agency Cost - Mariana Sari Dewi; Driana Leniwati (Jurnal Ilmiah Manajemen Kesatuan, 2026)
This study aims to analyze the effect of discretionary bonuses on employee performance through the mediating role of distributive justice, procedural justice, and agency cost in a state-owned enterprise subsidiary operating in port equipment maintenance services. The study employed a quantitative approach using census sampling of 110 employees. Data analysis used SEM-PLS through SmartPLS 4.0. Results showed that discretionary bonus has a positive significant effect on distributive justice (β=0.679), distributive justice has a positive significant effect on procedural justice (β=0.500), procedural justice has a negative significant effect on agency cost (β=-0.349), agency cost has a negative significant effect on employee performance (β=-0.221), and distributive justice, procedural justice, and agency cost serially mediate the relationship between discretionary bonus and employee performance with complementary partial mediation pattern (β=0.026). The research model explained 60.8% of variance in employee performance. This study concludes that discretionary bonus effectiveness depends on employees’ fairness perception, thus its implementation should consider distributive and procedural justice principles to suppress agency cost and improve performance.